2023
DOI: 10.3390/pathogens12020185
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Tick-Borne Encephalitis (TBE) Virus Antibodies in Wild Rodents from Two Natural TBE Foci in Bavaria, Germany

Abstract: Tick-borne encephalitis (TBE) is Eurasia’s most important tick-borne viral disease. Rodents play an important role as natural hosts. Longitudinal studies on the dynamics of the seroprevalence rates in wild rodents in natural foci over the year are rare, and the dynamics of the transmission cycle still need to be understood. To better understand the infection dynamics, rodents were captured in a capture-mark-release-recapture-study in two natural foci in Bavaria, Germany, monthly from March 2019 to October 2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Furthermore, a thermosensitive RNA switch has been proposed as significant for virus propagation in ticks [ 48 ]. However, other factors such as duration of photoperiod, relative humidity [ 8 , 26 ], age and sex [ 49 ], reproductive and immune status [ 50 ], and tick burden load on rodents [ 51 ], which are also at least partially related to the average air temperature, might be influential. Moreover, a rapid fall in ground-level temperatures in August and October is associated with the synchrony of larval-nymphal questing (and therefore co-feeding) in early spring, which was observed in TBEV foci and not elsewhere [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a thermosensitive RNA switch has been proposed as significant for virus propagation in ticks [ 48 ]. However, other factors such as duration of photoperiod, relative humidity [ 8 , 26 ], age and sex [ 49 ], reproductive and immune status [ 50 ], and tick burden load on rodents [ 51 ], which are also at least partially related to the average air temperature, might be influential. Moreover, a rapid fall in ground-level temperatures in August and October is associated with the synchrony of larval-nymphal questing (and therefore co-feeding) in early spring, which was observed in TBEV foci and not elsewhere [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wild-living rodents play an important role as TBP reservoir animals in nature [ 73 ]. Our study showed the presence of the genetic material of Borrelia spp., Ehrlichia spp., Bartonella spp., and Mycoplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Natural TBE Foci in Bavaria, Germany-By Brandenburg et al [13] While B. miyamotoi discussed above [11] is an emerging disease tick-borne encephalitis (TBE) is one of the most important TBD in areas of Asia and Europe. TBE has been a notifiable disease in the European Union since 2012.…”
Section: Seroprevalence Of Tick-borne Encephalitis (Tbe) Virus Antibo...mentioning
confidence: 99%